Associação entre noctúria e quedas: resultados de um estado populacional em idosos do sexo masculino no município de São Paulo - Rustom Júnior, Jorge Salim [UNIFESP] (2009)
To evaluate the association between nocturia and falls in a group of communityliving elderly men in the city of São Paulo (Brazil). Methods: Under the coordination of the Pan American Health Organization and World Health Organization, a multicenter study named Health, Welfare and Aging (SABE Study) is being conducted to evaluate the living and health conditions of older people in Latin America and Caribbean. In Brazil, this study is evaluating the elderly population (60 years or more) in São Paulo since 2000. In each cycle of participants evaluations, the data are collected simultaneously, by an average of houses chosen for interviews conduction, using a standardized instrument composed of eleven thematic sessions: personal, cognitive status, health status, functional status, medications, use and access to services, network of social support, and family and occupational history. A detailed description of the methodology used is available in the PAHO website. To develop this study, the sessions A (personal data) and C (health status) were used. The presence of nocturia was taken to be a independent dichotomous variable, and this was ascertained as the response “yes” to the question “Do you need to void three times or more at night?” .The presence of falls was also taken to be a dependent dichotomous variable, and this was ascertained as the response “yes” to the question “Did you have any fall during the last 12 months?” For both questions, the categories “Does not know” and “No response” were disregarded and were then considered to be missing values. The subjects were divided into five groups according to age (60-64 years, 65-69 years, 70-74 years, 75-79 years and 80 years or more). The intergroup analysis used was the logistic regression. Results: 865 men were interviewed, mean age 68 years. It was observed high prevalence of nocturia and falls in all groups, with higher prevalence of both in the eldest group (p <0.001). However, the association of nocturia and falls was not statistically significant in any of the groups (p = 0.45). This is one of the pioneering studies that assess only the male population, showing that nocturia was not significantly associated with falls. However, it was observed high prevalence of nocturia and falls in all groups of participants, especially in men older than 80 years. It is suggested that nocturia is a common symptom in the elderly, but nocturnal micturition does not increase the prevalence of falls in this group. Conclusion: Nocturia and falls are highly prevalent conditions in the elderly, but no association was found between both, so that these variables may be correlated to age and other clinical conditions.